FEMME LIFE ON THE SCREEN: ONLINE METHODS FOR SUBCULTURAL RESEARCH AND SURVIVAL - Schwartz, Andi (AoIR Selected Papers of Internet Research, 2020)
In this presentation, I will share key findings from my dissertation research on femme internet culture. Following the conference theme, this presentation will focus on the use of online methods for documenting subcultural life, and online subculture’s ability to make life more liveable for marginalized subjects. In this project, I define “femme” as a queer identity that is marked by a critical and political engagement with femininity that manifests through one’s style and values. I used Ulrika Dahl’s (2011) femme-inist ethnography methodology to conceptualize a study of “one’s own community.” In this presentation, I will focus on key findings about femme memes and online femme networks. My research demonstrates that through a study of a subculture’s memes, we can come to learn much about the group’s values, norms, and boundaries. Memes allow individuals to see one’s self, identity, or experiences reflected, or be “in on the joke.” Femmes recognize the experiences specific to femme subjectivity (ie. femme invisibility) communicated through memes and feel a sense of connection with one another. In addition, my research offers further evidence of the value of online communities for marginalized subjects. The femmes in my study used online connections to combat geographical isolation, create intergenerational bonds, and even find a reason to stay alive. My research shows that the technological affordances of Instagram continue to make online communities valuable. In addition, online methods are valuable tools to develop deeper insight into existing subcultures, especially those that are marginalized in more mainstream and/or public arenas.